Wound Healing Property Review of Siam Weed, Chromolaena odorata - Sirinthipaporn, Anushika; Jiraungkoorskul, Wannee (Pharmacognosy Reviews)
Chromolaena odorata (Family: Asteraceae) synonyms as Eupatorium odoratum is a traditional medicinal plant that is widely used for its wound healing property. In particular, the several parts of this herb have been used to treat wounds, burns, and skin infections. Furthermore, it has also been shown to possess anticancer, antidiabetic, anti‑hepatotoxic, anti‑inflammatory, antimicrobial, and antioxidant properties. Its phytochemical components are alkaloids, flavonoids, flavanone, essential oils, phenolics, saponins, tannins, and terpenoids. The other important constituents of this plant are Eupolin, chromomoric acid, quercetagetin, and quercetin, all of which contribute to its remedial properties. Published information on the wound healing property of C. odorata was gathered by the use of different scientific websites such as Google Scholar, Science Direct, PubMed, and Web of Knowledge to provide an up‑to‑date review showing its importance.
Keywords: Antioxidant; Chromolaena odorata; healing property; plant; traditional medicine; wound